2002
DOI: 10.1016/s0014-5793(02)02985-x
|View full text |Cite
|
Sign up to set email alerts
|

The human dynamin‐related protein OPA1 is anchored to the mitochondrial inner membrane facing the inter‐membrane space

Abstract: Mutations in the OPA1 gene are associated with autosomal dominant optic atrophy. OPA1 encodes a dynaminrelated protein orthologous to Msp1 of Schizosaccharomyces pombe and Mgm1p of Saccharomyces cerevisiae, both involved in mitochondrial morphology and genome maintenance. We present immuno-£uorescence and biochemical evidences showing that OPA1 resides in the mitochondria where it is imported through its highly basic amino-terminal extension. Proteolysis experiments indicate that OPA1 is present in the inter-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
278
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(301 citation statements)
references
References 31 publications
18
278
0
5
Order By: Relevance
“…Since whole embryo AIF knockouts are embryonic lethal, we generated conditional forebrain deficient AIF mice to study the role of AIF in neurons. We first observed that AIF −/− neurons exhibited fragmented mitochondria with dilated mitochondrial cristae and defective mitochondrial respiration, which is similar to Opa1 knockdown cells [132,145]. EM studies of neurons expressing the unreleasable form of AIF showed elongated mitochondria and tighter cristae tubules.…”
Section: Mitochondrial Cristae Structure and Cell Death: Demolition Fmentioning
confidence: 66%
See 1 more Smart Citation
“…Since whole embryo AIF knockouts are embryonic lethal, we generated conditional forebrain deficient AIF mice to study the role of AIF in neurons. We first observed that AIF −/− neurons exhibited fragmented mitochondria with dilated mitochondrial cristae and defective mitochondrial respiration, which is similar to Opa1 knockdown cells [132,145]. EM studies of neurons expressing the unreleasable form of AIF showed elongated mitochondria and tighter cristae tubules.…”
Section: Mitochondrial Cristae Structure and Cell Death: Demolition Fmentioning
confidence: 66%
“…The third GTPase required for mitochondrial fusion is localized to the intermembrane space and is called Opa1 [86][87][88][89]. Opa1 (Optical Atrophy 1) is imported into the mitochondrial inner membrane where it undergoes a regulated cleavage event to release a soluble shorter form of the protein into the intermembrane space.…”
Section: Mitochondrial Fusion Proteinsmentioning
confidence: 99%
“…OPA1 and its orthologues, encoded by a single nuclear gene, are the only proteins belonging to the dynamin family that are located inside mitochondria. 7,24,25 In yeast, Mgm1 appears in Western blots as doublet, the fast migrating form resulting from the cleavage by a mitochondrial rhomboid-like protease of the slow migrating form. 26,27 In human and mouse cell lines, previous works have reported the presence of 2-5 different electrophoretic forms of the OPA1 protein, 7,11,19 which also result from different proteolytic cleavages.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] The outer and inner mitochondrial membrane (OMM and IMM) dynamics crosstalk and involve large GTPases: respectively, the mitofusins Mfn1 and Mfn2 4,5 and the dynamin-related DRP1 6 on the OMM, and the dynaminrelated OPA1, localized in the inter membrane space (IMS). 7 Mitochondrial fission is tightly associated to the apoptotic process, and physical and functional interactions between apoptotic proteins including Bcl2-homologue domains and DRP1 and mitofusins have been identified. 8 In addition, BH3-only proapoptotic proteins, exemplified by tBid and Bik, might act directly on the IMM structure, although their intramitochondrial target remains unknown.…”
mentioning
confidence: 99%
“…79,80 It should be noted that Paraplegin faces the matrix and that the mitochondrial processing peptidase already trims most of the matrix residues of Opa1. 81 At this stage a plausible scenario deserving further investigation is that Paraplegin and Parl somehow cooperate in the cleavage of Opa1. For example, Paraplegin (or one of the other mAAA proteases that form the mAAA complex with paraplegin 82 ) could participate in the activation of Parl at the level of its N-terminal Pb domain.…”
Section: Parl: a Shortcut To Regulate Apoptosismentioning
confidence: 99%